Synthesis and mechanism-of-action of a novel synthetic antibiotic based on a dendritic system with bow-tie topology - Revilla-Guarinos, Ainhoa; Popp, Philipp F.; Dürr, Franziska; Lozano-Cruz, Tania; Hartig, Johanna; de la Mata, Francisco Javier; Gómez, Rafael; Mascher, Thorsten (Frontiers in Microbiology, 2022)
Over the course of the last decades, the continuous exposure of bacteria to antibiotics – at least in parts due to misprescription, misuse and misdosing – has led to the widespread development of antimicrobial resistances. This development poses a threat to the available medication in losing their effectiveness in treating bacterial infections. On the drug development side, only minor advances have been made to bring forward novel therapeutics. In addition to increasing the efforts and approaches of tapping the natural sources of new antibiotics, synthetic approaches to developing novel antimicrobials are being pursued. In this study, BDTL049 was rationally designed using knowledge based on the properties of natural antibiotics. BDTL049 is a carbosilane dendritic system with bow-tie type topology, which has antimicrobial activity at concentrations comparable to clinically established natural antibiotics. In this report, we describe its mechanism of action on the Gram-positive model organism Bacillus subtilis. Exposure to BDTL049 resulted in a complex transcriptional response, which pointed towards disturbance of the cell envelope homeostasis accompanied by disruption of other central cellular processes of bacterial metabolism as the primary targets of BDTL049 treatment. By applying a combination of whole-cell biosensors, molecular staining, and voltage sensitive dyes, we demonstrate that the mode of action of BDTL049 comprises membrane depolarization concomitant with pore formation. As a result, this new molecule kills Gram-positive bacteria within minutes. Since BDTL049 attacks bacterial cells at different targets simultaneously, this might decrease the chances for the development of bacterial resistances, thereby making it a promising candidate for a future antimicrobial agent.